Canon 427: Diocesan Administrator and College of Consultors - Waters, Ian Benjamin (Roman Replies and CLSA Advisory Opinions 2014, 2014)
During the vacancy of our diocese, what are the protocols to be observed when the diocesan administrator calls a meeting of the diocesan consultors? Specifically, assuming that all consultors are invited and have received meeting papers, wheether there is a quorum required or whether a simple majority of those attending is sufficient?